Structure-properties relationship of the derivatives of carbazole and 1, 8-naphthalimide: Effects of the substitution and the linking topology. (March 2015) - Gudeika, Dalius; Grazulevicius, Juozas Vidas; Volyniuk, Dmytro; Butkute, Rita; Juska, Gytis; Miasojedovas, Arunas; Gruodis, Alytis; Jursenas, Saulius
Abstract: Nine compounds having electron-accepting 1, 8-naphthalimide and electron-donating carbazole moieties were synthesized employing palladium-catalyzed C–N and C–C coupling reactions and characterized by the thermal methods, absorption and emission spectrometry, electrochemical and photoelectrical tools. The synthesized compounds possess high thermal stability with the 5% weight loss temperatures being in the range of 351–476 °C. Most of the synthesized compounds are capable of glass formation with glass transition temperatures ranging from 30 to 87 °C. The cyclic voltammetry measurements showed that the solid state ionization potentials values of the carbazole and 1, 8-naphthalimide derivatives range from 5.46 eV to 5.76 eV and the electron affinities values range from −3.04 eV to −2.92 eV. Dilute solutions of the 3- and 3, 6-naphthalimide-substituted derivatives of carbazole in polar solvents were found to emit in the green region with quantum yields ranging from 0.66 to 0.83, while in the solid state fluorescence quantum yields were found to be in the range of 0.01–0.45. ((E)-9-((( N -(2-ethylhexyl)-1, 8-naphthalimide)-4-yl)ethenyl)-9 H -carbazole) exhibited efficient fluorescence in the solid state with quantum yield as high as 0.45. The effects of the linking topology of the chromophores and of the incorporated alkyl substituents on the thermal, optical, and photoelectrical properties of the synthesized donor-acceptor compounds are analyzed. The impact of the ground state intramolecular twisting of the carbazole and naphthalimide moieties induced by the substituents resulting in significant variation in the rates of radiative and nonradiative excitation deactivation is revealed. Highlights: Donor-π-acceptor type derivatives of 1, 8-naphthalimide and carbazole. High thermal stability with the 5% weight loss temperatures up to 476 °C. Efficient fluorescence in the solid state with quantum yield up to 0.45. Almost flat configuration of the molecules having ethenyl-containing linkage between chromophores.